2016
DOI: 10.1093/mnras/stw1383
|View full text |Cite
|
Sign up to set email alerts
|

On the properties of compact groups identified in different photometric bands

Abstract: Historically, compact group catalogues vary not only in their identification algorithms and selection functions, but also in their photometric bands. Differences between compact group catalogues have been reported. However, it is difficult to assess the impact of the photometric band in these differences given the variety of identification algorithms. We used the mock lightcone built by Henriques et al. (2012) to identify and compare compact groups in three different photometric bands: K, r, and u. We applied … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
13
1
Order By: Relevance
“…The slight differences are caused by the wavebands, lightcones, and galaxy blending method. Similarly, the fraction of Real CGs found by Díaz-Giménez & Zandivarez (2015) (DGZ15) and Taverna et al (2016) (TDGZ16) were slightly higher than what we find here, but this is because we only compare here to our modified algorithm, which produces a lower fraction of Real CGs. Also, the fraction of Real CGs found with the GII SAM was higher in Díaz-Giménez et al…”
Section: Effects Of the Other Parameterscontrasting
confidence: 50%
See 2 more Smart Citations
“…The slight differences are caused by the wavebands, lightcones, and galaxy blending method. Similarly, the fraction of Real CGs found by Díaz-Giménez & Zandivarez (2015) (DGZ15) and Taverna et al (2016) (TDGZ16) were slightly higher than what we find here, but this is because we only compare here to our modified algorithm, which produces a lower fraction of Real CGs. Also, the fraction of Real CGs found with the GII SAM was higher in Díaz-Giménez et al…”
Section: Effects Of the Other Parameterscontrasting
confidence: 50%
“…Moreover, DGM10 found that the frequency (space density) of CGs was roughly 10 times higher in the simulations than observed, suggesting that the HCG sample was 90 per cent incomplete, mainly in groups dominated by a single galaxy (as previously noted by Prandoni et al 1994). In subsequent studies by our team (Díaz-Giménez et al 2012;Díaz-Giménez & Zandivarez 2015;Taverna et al 2016;Díaz-Giménez et al 2018), CGs were extracted from the public outputs of different SAMs based on different physics or from those of older SAMs run on the dark matter haloes extracted from cosmological simulations run with different cosmological parameters. These studies led to different fractions of physically dense groups.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…1983;Nolthenius & White e.g. 1987; see also Table 5 in Díaz-Giménez et al 2012, Taverna et al 2016 and references therein). Here we invoke an algorithm with a set of tunable parameters that allows us to investigate how the demographics of a CG sample depend on individual parameters.…”
Section: Identification Of Cgs In the Millennium Simulation Galaxy Camentioning
confidence: 99%
“…The surveys have different apparent magnitude limits, different wavebands, and may or may not have spectroscopic information. Galaxies selected in different wavebands will form groups with different physical characteristics (Taverna et al 2016). In addition, the limits imposed in the criteria are arbitrary and can change depending on the identifier.…”
Section: Introductionmentioning
confidence: 99%